Can bone mineral density loss in the non-weight bearing distal forearm predict mortality? - Hauger, Annette Vogt; Bergland, Astrid; Holvik, Kristin; Emaus, Nina; Strand, Bjørn Heine (Bone, 2020)
Purpose - Low bone mineral density (BMD) is associated with increased risk of fractures and mortality. We investigated if rate of BMD loss in the distal forearm over seven years predicted mortality. Methods - 1725 postmenopausal women and 1879 men aged 50–74 who participated in the longitudinal Tromsø Study waves 4 (1994–95) and 5 (2001−2002) were included. Cox regression models adjusted for lifestyle- and health related variables were used to assess associations between BMD change over seven years and subsequent mortality during up to 17 years of follow-up in participants with normal and low BMD at baseline. Results - Baseline BMD decreased and seven-year bone loss increased with increasing age. Overall, mortality rates were higher among those with low versus normal BMD (38 vs 19 per 1000 py in women, 56 vs 34 in men) and at higher bone loss rates (rate ratio high:low = 1.2 in women, 1.7 in men). BMD change was associated with increased mortality only in men with normal baseline BMD. In this group, men with a BMD loss of >4% had significantly higher mortality (HR 1.50, 95% CI 1.21, 1.87) than men with increased or unchanged BMD. BMD change was not significantly associated with increased mortality in women or in men with low BMD at baseline. Conclusions - BMD loss in the distal forearm was associated with increased mortality in men with normal BMD at baseline, but not in women. We found no clear association between BMD loss and mortality in those with low BMD at baseline.